Analisis Variasi Genetik Gen Angiotensinogen M235T pada Penderita Stroke Iskemik di Rumah Sakit Umum Pusat Dr. Kariadi, Semarang secara Polymerase Chain Reaction Restriction Fragment Length Polimorfism (PCR- RFLP) - Tugasworo, Dodik; Retnaningsih, Retnaningsih; Kurnianto, Aditya; Suryadi, Suryadi; Rahmawati, Dani; Rahmayanti, Rahmayanti; Budiman, Jethro (RSUP Dr. Kariadi, 2023)
Background: Stroke is the leading cause of death and disability in the world. The incidence of ischemic stroke is influenced by genetic factors, environmental factors and their interactions. Genetic variation of the Angiotensinogen (AGT) M235T gene is associated with hypertension and diabetes mellitus, which are risk factors for stroke. Objective: To examine the genetic variation of the Angiotensinogen M235T gene in patients with Ischemic Stroke treated at Dr. Kariadi General hospital, Semarang. Method: The subjects of the study were 72 ischemic stroke patients who were treated at the outpatient clinic of the Neurology Department Dr. Kariadi Semarang in January - December 2013. DNA extraction of research subjects was performed at the CEBIOR laboratory, Diponegoro National Hospital from January to March 2020. Amplification was performed with Polymerase Chain Reaction (PCR). Digestion of PCR products was using Restriction Fragment Length Polymorphism (RFLP) method. Results: Out of 72 samples, the AGT M235T CT were found in 37 samples (51.4%), the AGT M235T TT gene was found in 35 samples (48.6%) and no samples showed the AGT M235T CC. Conclusion: There are 3 types of genetic variants of the AGT M235T gene, including the AGT M235T CT, the AGT M235T TT and the AGT M235T CC. Among the three types of variants, the variant of the AGT M235T CT gene is the most common variant found in ischemic stroke patients treated at the Dr. Kariadi General Hospital Semarang.